Trade Integration and Business Cycle Synchronization : A Reappraisal with Focus on Asia - Duval, Romain; Cheng, Kevin; Hwa Oh, Kum.; Saraf, Richa (Washington, D.C. : International Monetary Fund, 2014)
This paper reexamines the relationship between trade integration and business cycle synchronization (BCS) using new value-added trade data for 63 advanced and emerging economies during 1995-2012. In a panel framework, we identify a strong positive impact of trade intensity on BCS-conditional on various controls, global common shocks and country-pair heterogeneity-that is absent when gross trade data are used. That effect is bigger in crisis times, pointing to trade as an important crisis propagation mechanism. Bilateral intra-industry trade and trade specialization correlation also appear to increase co-movement, indicating that not only the intensity but also the type of trade matters. Finally, we show that dependence on Chinese final demand in value-added terms amplifies the international spillovers and synchronizing impact of growth shocks in China.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet